Batch and Column Arsenate Sorption Using Turbinaria ornata Seaweed Derived Biochar: Experimental Studies and Mathematical Modeling. Issue 12 (25th March 2020) - Saravanakumar, Krishnan; Senthilkumar, Ramalingham; Prasad, Donipathi Mogili Reddy; Prasad, Balakrishna Sankari Naveen; Manickam, Sathyamoorthy; Gajendiran, Vasu
Abstract: The ability of Turbinaria ornata seaweed derived biochar (TOB) to remove arsenate ions from polluted solutions in batch and column trials has been investigated. The biochar, produced at 300 °C and 120 min through pyrolysis, exhibited maximum arsenate sorption capacity at pH 4. Batch sorption isotherm was described with different models (Freundlich, Langmuir and Sips) and the Sips model best described the experimentally derived isotherm with high correlation coefficient and low percentage error values. The maximum arsenate sorptional capacity calculated using the Langmuir model was estimated to be 0.124 mmol/g (at pH 4; 2 g/L biochar dosage and 0.5 mmol/L initial arsenate concentration). For elution trials, 0.01 M NaOH performed well to desorb arsenate from arsenate‐bounded TOB with elution efficiency greater than 99.6% with no significant damage to TOB. The capability of TOB to sorb arsenate continuously was examined in a packed column. The continuous trials were mainly performed to evaluate the impact of influential column parameters including bed height, initial arsenate concentration and flow rate. The arsenate sorptional capacity declined with improvement in flow rate, whereas enhanced with increment in bed depth and initial arsenate concentration values. Regeneration of exhausted TOB was possible with 0.01 M NaOH. After three sorption‐elution cycles it was determined that TOB exhibited superior sorption capacities and percentage removal efficiencies. Abstract : The toxic arsenate ions from contaminated water were remediated using biochar prepared from brown alga Turbinaria ornata in batch and column mode of operations. The biochar performed well in arsenate removal with maximum batch sorption capacity of 0.124 mmol/g and column sorption capacity of 0.109 mmol/g. The biochar‐loaded column was successfully regenerated and reused for three sorption‐desorption cycles using 0.01 M NaOH as elutant.